Best Answer

-4x2 - 32x + x + 8 = 8x2 - 56x : simplify and group the various terms

-32x + 56x + x + 8 = 8x2 + 4x2

25x + 8 = 12x2 : Now present this as a standard quadratic equation.

12x2 - 25x - 8 = 0 : Solving for the roots of a quadratic equation gives :-

x = [25 ± √(252 + 4x12x8)] ÷ 2x12 = [25 ± √1009] ÷ 24 = [25 ± 31.765] ÷ 24

x = 56.765/24 = 2.365 and x = -6.765/24 = -0.282

x = 2.365 and -0.282

Study guides

☆☆

Q: What is the answer to -4x2 minus 32x plus x plus 8 equals 8x2 minus 56x?

Write your answer...

Submit

Still have questions?

Related questions

64

(2x - 7)(2x - 9)

4x2 plus 3=11

y=4x2+3x+8

64

4x^2 + 32x + 64 = 4(x^2 + 8x + 16) = 4(x + 4)^2 = 4(x + 4)(x + 4)

4x2+49x+90 = (4x+9)(x+10) when factored

There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.

[ x3 - 4x2 + 7x ] / (x) = x2 - 4x + 7

4(x^2 + 8x + 160)

4x2 = -12x, divide both sides by 4x: x = -3

No.

People also asked